Investigation of key autophagy-and mitophagy-related proteins and gene expression in BALF cells from patients with IPF and RA-ILD - Vasarmidi, Eirini (Mol Med Rep, 2018)
Idiopathic pulmonary fibrosis (IPF) is a chronic and irreversible interstitial lung disease with a poor prognosis and limited therapeutic options. Over the past decade, research efforts have focused on the pathogenetic mechanisms involved in this enigmatic lung disease. Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease often complicated by the development of interstitial lung disease (ILD), leading to high mortality and morbidity. Autophagy is a process regulating the turnover of subcellular components and organelles, and represents a major cellular homeostatic mechanism. Recent evidence suggests a role of autophagy and mitochondrial dysfunction in the development of IPF, focusing on lung fibroblasts and epithelial cells. The aim of this study was to examine the mRNA levels of molecules involved inthe autophagy pathway in bronchoalveolar lavage fluid (BALF)-derived cellsfrom patients with IPF in comparison topatients with RA demonstrating lung involvement (ILD) by RT-qPCR. The significant upregulation of BECLIN1 was observed in patients with RA-ILD compared with those with IPF. Other genes involved in the autophagy pathway were also examined, such as Unc-51 like autophagy activating kinase 1 (ULK1), BCL2 interacting protein 3 (BNIP3) and p62. No differences in the mRNA expression levels of these genes were observed. As regards the selective degradation of mitochondria and mitophagy, similar PTEN-induced putative kinase 1 (PINK1) and PARKIN; E3 ubiquitin ligase (PRKN) expression, as well as PINK1 protein levels, were observed. On the whole, the findings of this study demonstrate an increased expression of BECLIN1 in BALF cells from patients with RA-ILD compared with those from patients with IPF, while similar levels in other key molecules implicating in the autophagy pathway were observed in patients with IPF and RA-ILD.